2022
DOI: 10.1021/acs.oprd.1c00471
|View full text |Cite
|
Sign up to set email alerts
|

Process Development of Enantioselective Imine Reductase-Catalyzed Syntheses of Pharmaceutically Relevant Pyrrolidines

Abstract: Process development and optimization for an enzymatic reduction of 2-aryl-substituted pyrrolines to enantioselectively access the corresponding pyrrolidines have been carried out. Such chiral pyrrolidines are of high pharmaceutical interest and represent structural subunits in, e.g., larotrectinib and MSC2530818. This work enables access to the heterocyclic amine products with full conversion (>99%), excellent enantioselectivity (>99% ee), and good to high yield (up to 91%) in the presence of a readily availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Of particular interest are products 3f and 3k , which are motifs featured in the APIs larotrectinib, and MSC2530818 (Figure ), respectively. In contrast, recent examples of the asymmetric synthesis of 2-aryl- N -heterocycles employing a reductive amination strategy using transition-metal catalysts are mostly limited to <90% ee , with only a few exceptions. Biocatalytic imine reduction using IREDs generally reaches >99 ee ; however, the starting imines for this strategy are typically not commercially available. Fanourakis et al reported the synthesis of ( R )- 3c in 33% yield and 89% ee starting from readily available 4-phenylbutan-1-ol by employing an asymmetric benzylic C-H activation strategy, followed by Mitsunobu cyclization and deprotection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest are products 3f and 3k , which are motifs featured in the APIs larotrectinib, and MSC2530818 (Figure ), respectively. In contrast, recent examples of the asymmetric synthesis of 2-aryl- N -heterocycles employing a reductive amination strategy using transition-metal catalysts are mostly limited to <90% ee , with only a few exceptions. Biocatalytic imine reduction using IREDs generally reaches >99 ee ; however, the starting imines for this strategy are typically not commercially available. Fanourakis et al reported the synthesis of ( R )- 3c in 33% yield and 89% ee starting from readily available 4-phenylbutan-1-ol by employing an asymmetric benzylic C-H activation strategy, followed by Mitsunobu cyclization and deprotection.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen-containing heterocycles represent a privileged structure in many APIs, and thus chiral cyclic amines are especially important building blocks. Several biocatalytic routes toward this moiety have been reported (Figure A); yet, an attractive strategy, biocatalytic reductive amination of a ketone bearing a leaving group, followed by spontaneous cyclization, remains to be explored (Figure B). ,, Only three examples have been reported in the literature, two of which produce the ( R )-enantiomer in the 2-position. , The third example generates a 3-substituted piperidine, but was abandoned during development due to the instability of the aldehyde starting material, and no data on conversions or yield were reported . Transaminases (TAs) are pyridoxal-5′-phosphate (PLP)-dependent enzymes catalyzing the transfer of an amino group from a sacrificial amine donor to a prochiral ketone substrate.…”
Section: Introductionmentioning
confidence: 99%
“…6 In recent decades, biocatalysis, for example, imine reductase (IRED)-based catalysis, has become a valuable tool for their synthesis. 7,8 One elegant synthetic methodology to get access to such heterocyclic amines is by means of preparation of imines or iminium ions by oxidative rearrangement, and their in situ conversion utilizing NaBH 4 as a reducing agent, thus forming the corresponding racemates as products. Several of such suitable chemical processes with integrated oxidative rearrangement techniques for this purpose have been described by Murai et al 9−11 For instance, the oxidative rearrangement using in situ generated N-chloroamines, which can be obtained by N-chlorination of the nitrogen of secondary amines when applying N-chlorosuccinimide (NCS), forms fused dihydroisoquinolines harboring iminium ions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…8,13 In this research field, in 2022 we already reported the enantioselective IRED-catalyzed reduction of 2-aryl-substituted pyrrolines, which are structurally related to those being accessible via oxidative rearrangement (2a). 8,11 This now led to the concept of merging the enantioselective, biocatalytic reduction step with oxidative rearrangement as access to these pyrrolines. 14 We selected imine 2b as our second model substrate due to its easy accessibility through oxidative rearrangement and its molecular structure similarity with the imines known to be excellent substrates for IRED-catalyzed reductions, such as dihydroisoquinolines.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, no industrial application of IREDs has been demonstrated until now for the synthesis of chiral 2-substitued pyrrolidines. This is mainly because the native enzymes reported previously suffer from several drawbacks, including low activity, poor stability, and severe substrate inhibition, resulting in low substrate loading and space–time yield (STY). Therefore, engineered IREDs with high activity and robust stability are in great demand to overcome the deficiencies of WT enzymes and construct more practical processes for the synthesis of chiral 2-substitued pyrrolidines.…”
Section: Introductionmentioning
confidence: 99%